Penerapan Pelayanan Kesehatan Bagi Peserta BPJS yang Kurang Mampu Berdasarkan UU No. 24 Tahun 2011 Tentang Badan Penyelenggara Jaminan Sosial - Sonya Airini Batubara; Piters Alfredo Sihombing; Perimanta Riji Ginting; Heru Putra Perangin-Angin (Universitas Medan Area, 2020)
The implementation of health services is carried out through organizations to maintain and improve health, prevent and cure an illness and restore the health of disadvantaged people. The purpose of this study is to understand government policies and legal policies in the BPJS Health service delivery system for disadvantaged BPJS participants. The research method used by the writer is analytical descriptive method, which is a method that describes, examines, explains and analyzes a legal rule to solve an actual problem. Based on the results of the study, it was concluded that in order to fulfill and realize the rights of every citizen in obtaining appropriate health services and the government's obligation to provide health facilities as mandated by the 1945 Constitution and health is a Public Good, intervention from the Government is needed. Bearing in mind that the implementation of the BPJS is issued through a Law which regulates while the process of determining the implementation is strengthened through a decree or decree from an authorized state official such as a Government Regulation and Presidential Regulation at least 10 derivative regulations must be made to strengthen an BPJS implementation.The implementation of health services is carried out through organizations to maintain and improve health, prevent and cure an illness and restore the health of disadvantaged people. The purpose of this study is to understand government policies and legal policies in the BPJS Health service delivery system for disadvantaged BPJS participants. The research method used by the writer is analytical descriptive method, which is a method that describes, examines, explains and analyzes a legal rule to solve an actual problem. Based on the results of the study, it was concluded that in order to fulfill and realize the rights of every citizen in obtaining appropriate health services and the government's obligation to provide health facilities as mandated by the 1945 Constitution and health is a Public Good, intervention from the Government is needed. Bearing in mind that the implementation of the BPJS is issued through a Law which regulates while the process of determining the implementation is strengthened through a decree or decree from an authorized state official such as a Government Regulation and Presidential Regulation at least 10 derivative regulations must be made to strengthen an BPJS implementation.